Essentiality of respiratory activity for pentose utilization in thermotolerant yeast Kluyveromyces marxianus DMKU 3-1042 - Noppon Lertwattanasakul (2018)
By random integrative mutagenesis with a kanMX4 cassette in Kluyveromyces marxianus DMKU 3-1042, we obtained three mutants of COX15, ATP25 and CYC3 encoding a cytochrome oxidase assembly factor (singleton), a transcription factor required for assembly of the Atp9p subunit of mitochondrial ATP synthase and cytochrome c heme lyase, respectively, as mutants lacking growth capability on xylose and/or arabinose. They exhibited incapability of growth on non-fermentable carbon sources, such as acetate or glycerol, and thermosensitiveness. Their biomass formation in glucose medium was reduced, but ethanol yields were increased with a high ethanol level in the medium, compared to those of the parental strain. Experiments with respiratory inhibitors showed that cox15 and cyc3, but not atp25, were able to grow in glucose medium containing antimycin A and that the atp25 mutant was KCN-resistant. Activities of NADH and ubiquinol oxidases in membrane fractions of each mutant became a half of that of the parent and negligible, respectively, and their remaining NADH oxidase activities were found to be resistant to KCN. Absolute absorption spectral analysis revealed that the peak corresponding to a + a 3 was very small in atp25 and negligible in cox15 and cyc3. These findings suggest that the K. marxianus strain possesses an alternative KCN-resistant oxidase that is located between primary dehydrogenases and the ubiquinone pool and that the respiratory activity is essential for utilization of pentoses. © 2013 Springer Science+Business Media Dordrecht.